1994
DOI: 10.1136/bjo.78.11.810
|View full text |Cite
|
Sign up to set email alerts
|

Traditional eye medicine use among patients with corneal disease in rural Malawi.

Abstract: (BrJ7 Ophthalmol 1994; 78: 810-812)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
60
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 4 publications
6
60
2
Order By: Relevance
“…Studies in other parts of Nigeria and rural Malawi reported that 19.5-34.0% of patients with corneal ulcer had used TEM or steroid preparations before presentation. [8,10,19] Unlike other studies in Nigeria [6,[8][9][10] that reported no case of contact lens-related corneal ulcer, a female undergraduate student had corneal ulcer from contact lens (CL) use in our study. The cause was probably due to poor maintenance of the CL or cleaning solution.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Studies in other parts of Nigeria and rural Malawi reported that 19.5-34.0% of patients with corneal ulcer had used TEM or steroid preparations before presentation. [8,10,19] Unlike other studies in Nigeria [6,[8][9][10] that reported no case of contact lens-related corneal ulcer, a female undergraduate student had corneal ulcer from contact lens (CL) use in our study. The cause was probably due to poor maintenance of the CL or cleaning solution.…”
Section: Discussioncontrasting
confidence: 79%
“…Similar observations were made by Nwosu et al [8] and Chaha [24] in Nigeria and other workers in developing countries. [11,19] Gugnani et al [26] in Nigeria and Garg et al [27] in India reported Fusarium solani and Aspergillus species as common causes of keratomycosis. In southern Florida, United States, Liesegang et al [28] recorded a high incidence of Fusarium solani, also Vanzinni et al reported Fusarium solani as the most frequent agent of fungal keratitis (37.2%) in an eye care hospital in Mexico city.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional forms of eye treatment appear to cross all national and cultural barriers. Courtright et al  21 described the use of traditional eye medicines among patients with corneal diseases in rural Malawi. They found that rural patients, as in south India, commonly consulted traditional village healers even after receiving treatment from Western trained medical staff.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In the past, most studies examined the barriers to cataract surgery in adults only, which does not reflect the situation of cataract blind children. [7][8][9][10] In Malawi, at least a third of cataract blind children identified at outreach eye clinics did not attend the hospital within 3 months after being identified. 11 Reasons for the delay and/or non-attendance included poor communication between the health providers, families and communities; a lack of parental awareness of cataract being treatable; a complicated and poorly understood referral process; a lack of financial resources; distance to the hospital; and poor (perceived and actual) outcomes of surgery reinforcing fear associated with surgery.…”
Section: Introductionmentioning
confidence: 99%